Geomagnetically Induced Current Modeling in New Zealand: Extreme Storm Analysis Using Multiple Disturbance Scenarios and Industry Provided Hazard Magnitudes - D. H. Mac Manus; C. J. Rodger; M. Dalzell; A. Renton; G. S. Richardson; T. Petersen; M. A. Clilverd (Space Weather)
Abstract Geomagnetically induced currents (GICs) are induced in electrical power transmission networks during geomagnetic disturbances. Understanding the magnitude and duration of the GIC expected during worst‐case extreme storm scenarios is vital to estimate potential damages and disruptions to power networks. In this study we utilize the magnetic field waveforms measured during three large geomagnetic storms and scale them to expected worst case extreme storm magnitudes. Multiple methods are used to simulate the varying magnitude of the magnetic field across the different latitudes of New Zealand. Modeled GIC is produced for nine extreme storm scenarios, each covering 1–1.5 days in duration. Our industry partners, Transpower New Zealand Ltd provided GIC magnitude and duration levels which represent a risk to their transformers. Using these thresholds various extreme storm scenarios predict between 44 and 115 New Zealand transformers (13%–35%) are at risk of damaging levels of GIC. The transformers at risk are largely independent of the extreme storm time‐variations, but depend more on the latitude variation scenario. We show that these at‐risk transformers are not localized to any specific region of New Zealand but extend across all regions and include most of the major population centers. A peak mean absolute GIC over a 60‐min window of 920–2,210 A and an instantaneous 1‐min time resolution maximum GIC of 1,590–4,920 A occurs for a worst‐case extreme storm scenario. We believe this is one of the first studies to combine a reasonable worst‐case extreme geomagnetic storm with validated GIC modeling and industry‐provided GIC risk thresholds.